Tretinoin (0.05% cream vs. 5% peel) for photoaging and field cancerization of the forearms: randomized, evaluator-blinded, clinical trial - Sumita, J. M.; Miot, H. A. [UNESP]; Soares, J. L. M.; Raminelli, A. C. P.; Pereira, S. M.; Ogawa, M. M.; Picosse, F. R.; Guadanhim, L. R. S.; Enokihara, M. M. S. S.; Leonardi, G. R.; Bagatin, E. (Wiley-Blackwell, 2018)
BackgroundTopical tretinoin cream is the gold standard treatment for skin ageing, particularly photoaging. The purpose of tretinoin peel was to obtain similar results, but in a shorter time, however, there have been few controlled trials on its effectiveness. ObjectiveTo compare efficacy and safety of tretinoin 0.05% cream and 5% as a peeling agent on photoaging and field cancerization of the forearms. MethodsClinical trial with therapeutic intervention, prospective, randomized (computer-generated randomization list), parallel, comparative (intrasubject) and evaluator-blinded (except for histology and immunohistochemistry), including 24 women (48 forearms) aged over 60 years who have not undergone hormone replacement and categorized as Fitzpatrick skin phototype II or III. The forearms of the participants were randomized for treatment with 0.05% tretinoin cream three nights a week, or 5% tretinoin peel every 2 weeks. The opinion of the participant, severity of photoaging, corneometry, profilometry, high-frequency ultrasound, histology (haematoxylin-eosin and Verhoeff stainings) and immunohistochemistry (p53, bcl-2, Ki67 and collagen I) were assessed. ResultsOne participant dropped out. The mean photoaging score reduced 20% and the mean actinic keratosis (AK) count reduced 60% with no difference between treatments. Three efficacy parameters showed opposite effects between the tretinoin treatments (P < 0.05%): (i) thickness of the corneal layer decreased with 0.05% tretinoin and increased by 5%; (ii) dermis echogenicity increased by 0.05% and decreased by 5% and (iii) Ki67 expression increased by 0.05% and decreased by 5%. There was good tolerability for both regimens. ConclusionTretinoin as a cream 0.05% or peeling (5%) is safe and effective for the treatment of moderate photoaging and forearm field cancerization. The cream was superior in improving ultrasonographic parameters of ageing. Peeling was shown a superior performance in the stabilization of field cancerization.